1999
DOI: 10.1038/sj.bjc.6690472
|View full text |Cite
|
Sign up to set email alerts
|

Animal products, calcium and protein and prostate cancer risk in the Netherlands Cohort Study

Abstract: Prostate cancer risk in relation to consumption of animal products, and intake of calcium and protein was investigated in the Netherlands Cohort Study. At baseline in 1986, 58 279 men aged 55–69 years completed a self-administered 150-item food frequency questionnaire and a questionnaire on other risk factors for cancer. After 6.3 years of follow-up, 642 prostate cancer cases were available for analysis. In multivariate case-cohort analyses adjusted for age, family history of prostate cancer and socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
128
3
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 36 publications
(75 reference statements)
11
128
3
2
Order By: Relevance
“…In the present study, we also conducted a comparable analysis to explore individual nutrient values and prostate cancer risk adjusted for the same confounders as the dietary patterns (Table VI). Similar to other studies, 56,57 we did not find any statistically significant and clear associations between estimates of nutrient intake and prostate cancer risk. Further, the magnitude of risk for nutrients is generally lower than that for dietary patterns.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we also conducted a comparable analysis to explore individual nutrient values and prostate cancer risk adjusted for the same confounders as the dietary patterns (Table VI). Similar to other studies, 56,57 we did not find any statistically significant and clear associations between estimates of nutrient intake and prostate cancer risk. Further, the magnitude of risk for nutrients is generally lower than that for dietary patterns.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of protein and especially dairy protein on IGF-I could be important, because high serum IGF-I levels have been associated with a moderately increased risk of prostate cancer in several large-scale prospective studies including EPIC (Renehan et al, 2004;Allen et al, 2007). However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While some large cohort studies (with 4500 cases) have reported significant positive associations between dairy products and/or calcium intake and risk Chan et al, 2001), others have not (Schuurman et al, 1999;Michaud et al, 2001;Rodriguez et al, 2003). A recent clinical trial of calcium supplementation (1200 mg day À1 ) in the prevention of colorectal adenomas found no significant increase in prostate cancer (70 cases) risk with supplementation in secondary analyses, and even a suggestion of a protective effect (Baron et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we adjusted for age (in continuous years) only, but later for the following potential confounders: body mass index (o22.5, 22.5 -o25.0, 25.0 -o27.5, or X27.5 kg m À2 ), physical activity (o1000, 1000 -2499, or X2500 kcal week À1 ), smoking (never, past, or current), total energy intake (in quartiles), alcohol intake (none, 1 -3, 4 -6, or Xseven drinks week À1 ), red meat intake (pthree servings month, 1 -2 servings week, or Xthree servings week À1 ), vegetable intake (psix servings week, 1 -2 servings day, or Xthree servings day À1 ), and paternal history of prostate cancer (no or yes). We repeated the above analyses, examining only fatal prostate cancer, owing to the suggestion from some previous studies that the association may be stronger with advanced or fatal prostate cancer Schuurman et al, 1999;Chan et al, 2001;Rodriguez et al, 2003).…”
Section: Data Analysesmentioning
confidence: 99%